Northwest history. Mining. Discovery. 1927-04-24 (1927)
Richmond ore better. Further improvement reported in winze. Three-foot body of high grade bulges to 25 feet of both grades. The continuity of copper-bearing ore in the Tamarac-Carlisle group of the Richmond Yukon has been proven to a depth of 170 feet, according to a report from Thomas Kerruish, superintendent, Whitehorse, Y.T., to the Spokane office of the company. This last 40 feet has been through a winze started from the 120-foot level. The winze will be continued to the 100-foot point or farther and further proof of continuity will be followed by an extension of the working shaft from the 120-foot level.